Effects of cumulative acidification of soil on element transfer in Pinus massoniana Lamb. forest at Dinghushan - LIU Ju-xiu; ZHOU Guo-yi (浙江大学学报. 农业与生命科学版)
Under the condition of natural acid deposition, the soil will be acidified gradually. Due to cumulative acidification of soil, transfer dynamics of K, Na, Ca, Mg, P, Fe, Mn, Cu and Al in the soil of mason pine forest at Dinghushan were changed, compared with the control. The exchangeable K content and available Fe and Cu content increased steadily, whereas available P and activated Al decreased, which was accompanied by earlier decrease and later increase in exchangeable Ca and Mg. Soil available Mn content was relatively stable. Total K and Na content steadily reduced in the soil leachate, with the Ca and Mg content tending to decrease at first and then remaining stable. Compared with the transfer dynamics of K and Na, changes in total P, Fe, Cu, Mn and Al concentrations in the soil leachate showed a contrary tendency. It is concluded that concentrations of available Fe, Mn and Al in soil and Mg, Mn and Al in the soil leachate in mason pine forest at Dinghushan were heavily affected by acid deposition. In rainy season, Ca and Mg content of pine leaves in mason pine forest exposed to simulated acid rain decreased with increasing acidity of simulated acid rain. It deserves our concern whether Mg and P will be deficient in mason pine forest. Exposure to acid deposition would probably lead to imbalance of nutrient elements in soil of the mason pine forest due to excessive decrease in Mg, P and Cu and activation of Al and Fe in soil.